PERBANDINGAN ESTIMASI ANGGARAN BIAYA ANTARA PEMERINTAH KABUPATEN BLITAR DENGAN PEMERINTAH KOTA BLITAR PADA PEMBANGUNAN JALAN TEMBUS DI JL. KURMA KOTA BLITAR - Prasetiyo, Nandang (Jurnal Qua Teknika, 2017)
The scientific work entilited Comparison of the estimated budget between the government kabupaten blitar with government blitar city on construction of access road in Jl. Kurma blitar City aims to knowing the cost of building a road through on jl. Kurma knowing the cost of building a road through on jl. Kurma to know the different costs of road construction budged breaks on jl.kurma with an estimated price of materials and wages of two distinct regionsThe study estimates the cost of the budget implemented in CV. EKA CONSULTANT with methods of primary and secondary data collectionOf the research budget estimates resulting cost difference significant budget lies in masonry work time